2014
DOI: 10.1177/1933719114522524
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Adenine Dinucleotide Phosphate Oxidase Expression Is Differentially Regulated to Favor a Pro-oxidant State That Contributes to Postoperative Adhesion Development

Abstract: We have previously reported that superoxide (O) contributes to the development of postoperative adhesions. In this study, we determined whether O generating nicotinamide adenine dinucleotide phosphate oxidase (NOX) is differentially expressed in normal peritoneal and adhesion fibroblasts and tissues. The NOX isoforms were measured utilizing Western blot, immunohistochemistry, high-performance liquid chromatography, and real-time reverse transcription polymerase chain reaction. Expression and activity of NOX we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Bleeding, cauterization, ischemia, infections, and conditions that may damage the peritoneum may trigger adhesions [5][6][7] . While numerous cells such as mesothelial cells, histiocytes, fibroblasts, and lymphocytes help in healing the injured area, they also play a role in the development of peritoneal adhesion [2][3][4][5] . It has been demonstrated that adhesions are often the result of improper healing due to injured peritoneal tissues associated with oxidative stress 2 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Bleeding, cauterization, ischemia, infections, and conditions that may damage the peritoneum may trigger adhesions [5][6][7] . While numerous cells such as mesothelial cells, histiocytes, fibroblasts, and lymphocytes help in healing the injured area, they also play a role in the development of peritoneal adhesion [2][3][4][5] . It has been demonstrated that adhesions are often the result of improper healing due to injured peritoneal tissues associated with oxidative stress 2 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Adhesions are the result of an improper and uncontrolled healing process due mainly to oxidative stress-related damage to peritoneal tissues. Five to seven days post-operatively, the adhesive bands turn into vascular permanent fibrous adhesions [8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The ethiopathogenesis of peritoneal adhesion formation is complex and involves inflammation, infection, ischemia, and oxidative stress [5,6,8,9]. Disequilibrium between the coagulation and fibrinolytic systems results in improper healing and peritoneal adhesive band formation between abdomino-pelvic organs [1,8].…”
Section: Introductionmentioning
confidence: 99%